APPLICATION OF ISCHEMIC COMPRESSION TECHNIQUE AND MYOFASCIAL RELEASE TECHNIQUE IN LUMBAL SPONDYLOSIS PATIENTS IN RATULANGI MAKASSAR MEDICAL CENTER - Suharto Suharto; Suriani Suriani (Media Kesehatan Politeknik Kesehatan Makassar, 2020)
Lumbar spondylosis is a condition of lower back pain caused by disc degeneration and facet joint which is characterized by osteophyte growth in the vertebral body precisely at the inferior and superior corpus edges, causing problems of pain, spasm, and impaired lumbar flexibility. The purpose of this study was to determine the difference in effect between the Ichemic compression technique (ICT) and Myofascial Release Technique (MRT) on the improvement of Lumbar Flexibility in patients with lumbar spondylosis, which was carried out at the Physiotherapy Clinic of TK II Pelamonia Hospital Makassar. The number of research subjects obtained as many as 20 people who meet the research criteria Then randomized into 2 groups: the treatment group I with ICT as many as 10 people and the treatment group II as many as 10 people with MRT. The research results show that the administration of Ichemic Compression Technique can increase lumbar flexibility with a mean difference 1,250. Whereas MRT administration can increase lumbar flexibility with a mean difference of 1,950. Wilcoxon test results of the treatment group I on the flexibility component obtained p value = 0.004 (p <0.05) while the treatment group II on the lumbar flexibility component obtained p value = 0.004 (p <0.05) which means that the provision of ICT with MRT can produce significant effect on increasing lumbar flexibility in patients with lumbar spondylosis. Mann Whitney test results on the lumbar flexibility component for treatment groups I and II p value = 0.035 (p <0.05). If seen from the mean values above, it can be concluded that the administration of Myofascial Release Technique (MRT) can result in a greater increase in lumbar flexibility compared to the Intermitten compression technique.  Keywords: Ichemic compression technique., Lumbar flexibility, Myofascial Release Technique, Lumbar Spondylosis